Deep hydrodenitrification of pyridine by solid catalyst coupling with ionic liquids under mild conditions. Issue 7 (6th March 2017) - Yao, Haoyu; Wang, Gang; Zuo, Cuncun; Li, Chunshan; Wang, Erqiang; Zhang, Suojiang
Abstract : A new route for deep hydrodenitrification (HDN) by solid catalyst coupling with ionic liquids (ILs) under mild conditions was proposed. Abstract : A new route for deep hydrodenitrification (HDN) by solid catalyst coupling with ionic liquids (ILs) under mild conditions was proposed. Ni2 P/SBA-15 activated at different temperatures were characterized with XRD, XPS, TG/DTA, and TEM and studied for further improvement. The deep HDN catalyzed by Ni2 P/SBA-15 coupling with different ILs was evaluated. [Bmim]BF4 was selected as the best one compared with [Emim]BF4, [Bmim]Cl and [Bmim]Br. The effect of reaction temperature, hydrogen pressure and the amount of IL on denitrification efficiency was investigated with parallel experiments using Ni2 P/SBA-15 coupling with [Bmim]BF4 . The N-removal efficiency increased from 27.09% to 73.48% after optimization. The IL system could be recycled for three times without a significant decrease in HDN activity. The coupled catalyzed HDN process and mechanism were also proposed and evaluated preliminarily through molecular simulation.